The distribution of KIR‐HLA functional blocks is different from North to South of Italy. Issue 3 (March 2014) - Fasano, M. E.; Rendine, S.; Pasi, A.; Bontadini, A.; Cosentini, E.; Carcassi, C.; Capittini, C.; Cornacchini, G.; Espadas de Arias, A.; Garbarino, L.; Carella, G.; Mariotti, M. L.; et al.
Abstract The killer cell immunoglobulin‐like receptor (KIR)–human leukocyte antigen (HLA) interaction represents an example of genetic epistasis, where the concomitant presence of specific genes or alleles encoding receptor–ligand units is necessary for the activity of natural killer (NK) cells. Although KIR and HLA genes segregate independently, they co‐evolved under environmental pressures to maintain particular KIR–HLA functional blocks for species survival. We investigated, in 270 Italian healthy individuals, the distribution of KIR and HLA polymorphisms in three climatic areas (from cold north to warm south), to verify their possible geographical stratification. We analyzed the presence of 13 KIR genes and genotyped KIR ligands belonging to HLA class I: HLA‐C, HLA‐B and HLA‐A. We did not observe any genetic stratification for KIR genes and HLA‐C ligands in Italy. By contrast, in a north‐to‐south direction, we found a decreasing trend for the HLA‐A3 and HLA‐A11 ligands (P = 0.012) and an increasing trend for the HLA‐B ligands carrying the Bw4 epitope (P = 0.0003) and the Bw4 Ile80 epitope (P = 0.0005). The HLA‐A and HLA‐B KIR ligands were in negative linkage disequilibrium (correlation coefficient −0.1211), possibly as a consequence of their similar function in inhibiting NK cells. The distribution of the KIR–HLA functional blocks was different along Italy, as we observed a north‐to‐south ascending trend for KIR3DL1, when coupled with HLA‐B Bw4 ligands (P = 0.0067) and with HLA‐B Bw4 Ile80 (P = 0.0027), and a descending trend for KIR3DL2 when coupled with HLA‐A3 and HLA‐A11 ligands (P = 0.0044). Overall, people from South Italy preferentially use the KIR3DL1‐HLA‐B Bw4 functional unit, while those from the North Italy equally use both the KIR3DL2‐HLA‐A3/A11 and the KIR3DL1‐HLA‐B Bw4 functional units to fight infections. Thus, only KIR3DL receptors, which exert the unique role of microbial sensors through the specific D0 domain, and their cognate HLA‐A and HLA‐B ligands are selectively pressured in Italy according to geographical north‐to‐south distribution.